Complexities of development management in the 2020s: Aligning values, skills and competencies in development studies. (15th July 2018) - Leslie, Helen M.; Banks, Glenn; Prinsen, Gerard; Scheyvens, Regina; Stewart‐Withers, Rochelle
Abstract : In the context of rapidly evolving development landscapes, the practice of development management has become increasingly complex. Trends, such as a decline in the overall volume of official development assistance, growing domestic inequality and the localisation agenda, are seeing a shift in the way aid is delivered and managed. This is requiring development managers from the Global North to be much more aware of their own values and world view and to be highly skilled in areas such as relationship management, communication, facilitation, ethics and advocacy alongside more traditional competencies such as monitoring and evaluation. Massey University's own research with the New Zealand global development sector supports this view and we have adapted our core development management course accordingly. Through pedagogy that is value‐based, ethically informed and practice‐orientated, we are working to equip our graduates to adapt to the complexities of development management. This includes prioritising ethics and relationship management and being aware of our responsibilities to Tangata Whenua as a Treaty‐led university. Our universities are well placed to offer the kind of innovative development studies education that will put our graduates and the communities that they serve on a pathway to better development outcomes in the 2020s.